2014
DOI: 10.1038/ncomms6354
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective hexa-hetero-functionalization of α-cyclodextrin an archetypical C6-symmetric concave cycle

Abstract: Access to C n (n44) symmetric cyclic concave molecules with a different function on each of their n subunits is an unmet challenge. The reason lies in the lack of a post-functionalization method whose site selectivity is sufficiently understood, predictable and modulable to access most functionalization patterns. Here we disclose a new site-directing rule for a debenzylation reaction on cyclodextrins that solves this problem and allows the unprecedented access to penta-and ultimately hexa-differentiations of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…[13,14] An impressiver ecent example has shown it is possible to orthogonally functionalize all six positions of a-CD. [17] Synthetic strategies that allow the selectivem odification of b-CD at the 2-, 3-, and 6-positions have also been reported. [18][19][20][21][22][23] Selective dior trisubstitution requires capping strategies, such as the use of biphenyl-based disulfonates.…”
Section: Introductionmentioning
confidence: 98%
“…[13,14] An impressiver ecent example has shown it is possible to orthogonally functionalize all six positions of a-CD. [17] Synthetic strategies that allow the selectivem odification of b-CD at the 2-, 3-, and 6-positions have also been reported. [18][19][20][21][22][23] Selective dior trisubstitution requires capping strategies, such as the use of biphenyl-based disulfonates.…”
Section: Introductionmentioning
confidence: 98%
“…For the synthesis of diametrically opposed diamine, Davis and co‐workers proposed a pathway requiring the synthesis of a capped β‐CD synthesized according to a modified procedure of Tabushi et al The reported yield is 12% for a three‐step procedure, improvement of this result had to be considered for our purpose. Some of us developed a strategy to access difunctional CDs by unprotecting a fully benzyl‐protected CD with DIBAL‐H . In the present work, we used this strategy to synthesize the 6 A ,6 D diamino β‐cyclodextrin (β‐CD(OH) 19 (NH 2 ) 2 ) in 55% yield and the 6 A ,6 D diamino 2 A ‐ G ,3 A‐G ,6 B ,6 C ,6 E ,6 F ,6 G nonadeca‐O‐benzyl‐β‐cyclodextrin (β‐CD(OBn) 19 (NH 2 ) 2 ) in 59% yield as precursors of linear polyamides.…”
Section: Resultsmentioning
confidence: 99%
“…For example, if a more soluble CD is required by the pharmaceutical industry, then random conversion of hydroxy groups into, for example, sulfate (or other hydrophilic) groups is performed. [29][30][31][32][33][34] Besides the substituted CDs described above, there are also other single-isomer derivatives -CDs persubstituted at the 2-, 3-or 6-positions. [27] When a single-isomer CD derivative is desired, the easiest way is through the preparation of a persubstituted derivative.…”
Section: General Methods For Synthesis and Characterisation Of Monosumentioning
confidence: 99%